Relationship Between Self-Report Heavy Alcohol Use, Fluid Poured and Internet Pornography Use in College Students - Bayer, R.; George, K.; Schneider, Amelia; Ackley, Brianne; Watson, Meredith; Matthews, Douglas (My University, 2018)
The purpose of this study was to see if heavy alcohol use and Internet pornography use significantly relate to one another. College students significantly over-pour a standard drink in a free-pour simulated alcohol pouring task, a finding that questions self-report alcohol consumption data (White et al., 2003; Zandy et al., 2013). Over-pouring a standard drink significantly correlates with self-report AUDIT scores, suggesting those who consume more alcohol engage in over-pouring more fluid in a simulated alcohol-pouring task.
Color poster with text, graphs, and charts.
Keywords: Posters; Internet pornography; Pornography--Social aspects; Alcohol consumption